2001
DOI: 10.4269/ajtmh.2001.64.147
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis c and cirrhotic liver disease in the Nile delta of Egypt: a community-based study.

Abstract: Abstract. Residents of Egypt's Nile river delta have among the world's highest seroprevalence of hepatitis C virus (HCV) infection. To assess the impact of HCV on chronic liver disease, we studied the association between HCV, other hepatitis viruses, and cirrhotic liver disease in a cross-sectional, community-based survey of 801 persons aged Ն 10 years living in a semi-urban, Nile delta village. Residents were systematically sampled using questionnaires, physical examination, abdominal ultrasonography and sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 25 publications
7
58
1
Order By: Relevance
“…The strong association of cirrhosis and HCC was supported by the evidences of its intermediating role in the pathogenesis of HCC due to chronic viral hepatitis [14]. In contrast to cirrhosis, the observed association between blood transfusion and HCC might be accounted for by its role in transmission of viral infection [15,37].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The strong association of cirrhosis and HCC was supported by the evidences of its intermediating role in the pathogenesis of HCC due to chronic viral hepatitis [14]. In contrast to cirrhosis, the observed association between blood transfusion and HCC might be accounted for by its role in transmission of viral infection [15,37].…”
Section: Discussionmentioning
confidence: 52%
“…In Egypt, several hospital-or community-based studies have tried to identify and establish associations between viral hepatitis and HCC over a decade [14,16,26,27]. The potential mode of transmission of HCV through occupational exposures and parenteral anti-schistosomal therapy (PAT) has also been discussed [28,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Others also reported that HCV infection with genotype 4a was the main cause of chronic liver disease in 135 adult patients living in Alexandria 27 and in 801 residents of a Nile Delta community. 28 Case-control studies have shown that both HBV and HCV infection increase the risk of HCC (adjusted odds ratios of [3][4][5][6][7][8][9][10][11][12][13]. Because the prevalence of infections with HCV in the country is so much higher than the prevalence of HBV infections, the attributable fraction of HCV (60%-70%) and the anti-HCV rate (75%-90%) has become the greatest risk factor for HCC in Egypt.…”
Section: Magnitude Of Hcv-caused Chronic Liver Disease In Egyptmentioning
confidence: 99%
“…Additionally, World Health Organization (WHO) fact sheets indicate that 130-150 million people globally have chronic hepatitis C infection, of which a significant number would develop liver cirrhosis or liver cancer and 500,000 yly mortality due to complications of late-stage liver diseases. In Egypt, the problem is even worse [4,5]. Approximately 20% of Egyptian blood donors are anti-hepatitis C virus (anti-HCV) positive [6,7].…”
Section: Introductionmentioning
confidence: 99%